Predicting Relationship between Mechanical Properties of Low Calcium Fly Ash-Based Geopolymer Concrete. Issue 4 (2nd October 2017) - Jindal, Bharat Bhushan; Parveen; Singhal, Dhirendra; Goyal, Ajay
ABSTRACT: This paper presents the results of the experimental study carried out on geopolymer concrete with the inclusion of alccofine. Efforts have been made to achieve the required compressive strength at ambient temperature. In the present investigation alccofine, richer in silica and finer than fly ash, has been added up to 10% of fly ash content. In addition, geopolymer concrete with different fly ash contents has been produced. The results are encouraging, as required compressive strength even 40 MPa could be achieved at ambient temperature. Compressive and tensile strength were increased with increase in fly ash and alccofine content. It was observed that better geopolymerization occured in presence of alccofine, and strength continuously increased significantly up to 90%. Attempts were further made to relate the compressive strength with splitting tensile and flexural strengths in presence of alccofine. A relationship has been suggested which holds good for geopolymer concrete with and without alccofine at ambiently, and heat cured specimens. GRAPHICAL ABSTRACT: